The Role of Economic Development in Export Performance in Islamic Countries - Sari, Vita Kartika; Yaumidin, Umi Karomah (Universitas Airlangga, 2024)
The necessity for a reevaluation of international trade has become increasingly apparent, particularly in Islamic countries. This study aims to estimate the economic development of selected Islamic countries, namely Egypt, Indonesia, Malaysia, Pakistan, Turkey, the United Arab Emirates, Brunei Darussalam, and Kuwait, in terms of export performance. This study was conducted within the broader context of Islamic countries, with a specific focus on analyzing dynamic panel data from 2010 to 2019. The dependent variable included exports of goods and services, while the regressors included GDP growth, broad money, and inflation. An estimation based on the panel generalized method of moments revealed a significant effect of export (-1) on export, a significant and negative impact of broad money on export, and a significant and positive effect on inflation. In contrast, GDP growth was not found to be significant. These findings are consistent with the high number of global Muslim consumers and the growth of Islamic finance assets. Currently, Islamic countries are prioritizing product diversification for both the Muslim and global markets. These findings indicate the need for increased economic development to achieve the practical implications of sustainable economic growth in Islamic economies.